(untitled) (Sociologisk Forskning, 1999)
Towards a transboundary democracy? Political responses to global environmental threats. Global environmental threats challenge the national state and the traditional understanding of democracy. Whereas many environmental problems transcend time and space, democracy is bound to the geographical borders of the national state as well as to its citizens/voters of today. The aim of this paper is to elaborate in what regards environmental problems challenge democracy and the sovereignty of national states, and critically discuss proposals for political reorganization. By analyzing two cases of global political mobilization against specific environmental threats, the possibilities for global responses to environmental threats are elucidated. By way of conclusion, the question is raised whether this kind of global alliances and actions implies a fragmentation of our understanding of the world, or if they are promising signs of a development towards global responsibility and cosmopolitan democracy.